Product awareness and sales promotion strategies among telecommunication industry consumers in Nigeria - Ismaila, Sikiru Monday (2023)
Customers have become more anxious about the economic situation over the past five years and have been looking for value. The number and depth of sales promotions and offers have increased across the market, but customers are not just looking for low prices, they are also looking to balance quality and the price they pay for things to make their budgets go further. As promotions become ever more prevalent, product loyalty is becoming outdated, so marketers need to get smart about the deals they offer. The business eco system is changing, especially the Nigerian telecommunication industry on a continuous basis owing to the level of competition which is moving at an alarming rate due to different competitor’s reaction patterns. Thus, the study was designed to investigate the effect of sales promotion strategies among telecommunication industry consumers in Benin Metropoliss, in Nigeria. The study employed the survey research method with questionnaire as the instrument for data gathering because of its capacity to elicit precise information for strategic decision making. The variables in this research refer are discount prices, product giveaways, loyalty point, demo and samples and product awareness. In this study, the population was on telecommunication users in Nigeria Benin, with the total population of 407 respondents comprising of both males and females. The sample size required was estimated by using a formula proposed by Bartlett et al. (2001). The findings show significant relationships between discounted price and product awareness (r = 0.287, p < 0.01), between product giveaways and product awareness (r = 0.285, p < 0.01), between loyalty point and product awareness (r = 0.368, p < 0.01) and between demos and samples (r = 0.428, p < 0.01) on product awareness. Also, the coefficient R (R= .522) revealed a significant moderate influence by the independent variables (discounted price, product giveaways, loyalty point, demos, and samples) on the dependent variable (product awareness). The regression analysis shows that discounted price, product giveaways, loyalty point, demos, and samples, jointly contributed 27.2 percent of the variance in product awareness. This suggested that to improve awareness on products, an effective and efficient marketing strategy is vital. Findings from the study revealed that service providers tended to over concentrate on the use of a narrow strategy of personal sales to attract patronage from people within their scope of operations. To cure this defect, it was recommended that the service providers should follow current global realities of using a combination of various IMC (Integrated Marketing Communications) methods to achieve greater results. It is therefore hoped that telecommunication network providers would endeavor to expand their strategies to include sales promotions, advertising messages, conditional sales as well as public relations strategies to target more customers. Consumers also would be able to make better decisions in selecting the telecommunication products.